The Effect of Critical Incident Learning Model on Student Engagement in Akidah Akhlak Education - Salsabila, Hanum; Dewi, Puti Andam; Rahmi, Siska Yulia; Sartini, Desti (El-Rusyd, 2026)
This study was motivated by the low level of student engagement in learning, as evidenced by uneven student participation in class, students’ reluctance to ask questions, answer, and express their opinions, and the limited variety of instructional models used. In addition, students often had difficulty understanding the problems presented by teachers because they were not directly related to their own experiences. This study aims to determine whether the Critical Incident learning model influences students’ learning engagement in Akidah Akhlak lessons. This is a quantitative study using a quasi-experimental method with a nonequivalent control group design. Data were collected using a questionnaire completed by the students. The study population consisted of 197 students, with a sample of 64 students: Class V.1 served as the experimental group and Class V.2 as the control group. The sampling technique used was non-probability purposive sampling. Based on the results of data analysis and discussion, the findings of this study are as follows. First, the learning engagement of students in Class V.2 without the use of the Critical Incident learning model had an average of -32%, falling into the low category. Second, the learning engagement of students in Class V.1 using the Critical Incident learning model had an average of 79%, falling into the active category. Third, the Critical Incident learning model has a significant effect on student learning engagement. This is supported by the results of the hypothesis test at a significance level of 0.05, which yielded a Sig. value of 0.00. Since Sig. 0.00 < 0.05, it can be concluded that H0 is rejected and Ha is accepted. This means that the Critical Incident learning model has an effect on students’ learning engagement in the Akidah Akhlak course.